Theophylline and Caffeine Content in Black Tea Produced in Burundi - Ndayirukiye, Alice; Ndikuryayo, Ferdinand; Mpawenayo, Pierre Claver; Ngezahayo, Jeremie; Gahungu, Godefroid (European Scientific Journal, ESJ, 2026)
To date, the specific levels of theophylline in Burundian tea remain unknown, and scientific information regarding caffeine content is limited. This study aims to address this gap by determining the content of these methylxanthines in different grades of black tea produced across the six main tea-growing regions of Burundi. Using High-Performance Liquid Chromatography (HPLC) based on the reference NTC-ISO 20481 method, samples collected from a dry-season production by Office du Thé du Burundi (OTB) and Promotion pour la Théiculture à Mwaro (PROTHEM) were analyzed. The results revealed that the theophylline content ranged from 0.145% to 0.279%, while caffeine levels varied between 1.979% and 3.331%. The significant variations (p < 0.05) depending on both the region and the tea grade were also revealed. Generally, the PD and D1 grades were identified as the richest in methylxanthines, with OTB-produced teas showing higher concentrations than those from PROTHEM. These findings confirm that Burundian tea is comparable to premium East African teas and remains within safe limits for daily consumption. The results of this study should help consumers to control the amount of these methylxanthines according to their nutritional needs, while Burundian black tea companies could use them to better promote this product and better position themselves on the international market.